“What condition will not miserable men accept?”: Hegemonic Masculinity in John Lyly’s Galatea - Paris, Jamie (Renaissance and Reformation / Renaissance et Réforme, 2020)
Studies of gender in John Lyly’s pastoral comedy Galatea (1592) have primarily focused on the queer potential of the female-to-male (FTM) crossdressing plot. While the critical focus on same-sex love and gender fluidity in the play has been evocative, it has understated the importance of hegemonic masculinity and biological gender determinism in the play. Neptune, Tityrus, and Melibeus, for example, reveal that their ways of being male are actually in competition with each other, quite inflexible, and closely monitored by the other men in the play. Moreover, while Phillida and Galatea become queer when they fall in love with each other, they begin the story with a view of gender as natural and immutable; they come to see gender as mutable only after Venus offers to perform the “unpossible” (5.3.154) to turn one of them into a man. This article will use R. W. Connell’s theory of hegemonic masculinity to argue that Neptune represents a rigid formation of hegemonic masculinity, and that Melibeus and Tityrus represent an ascendant form of hegemonic masculinity.